Study on Pain Catastrophizing From 2010 to 2020: A Bibliometric Analysis via CiteSpace - Luo, Huifang; Cai, Zongliao; Huang, Yanyi; Song, Jiating; Ma, Qing; Yang, Xiangwei; Song, Yang (Frontiers in Psychology, 2021)
Purpose: This study aimed to evaluate the global scientific output of research on pain catastrophizing and explore the hotspots and frontiers from 2010 to 2020 using bibliometric methods. Methods: Publications regarding pain catastrophizing published from 2010 to 2020 were extracted from the Web of Science Core Collection. CiteSpace was used to analyse the number of publications, countries, institutions, journals, authors, cited references, and keywords using standard bibliometric indicators. Results: A total of 1576 publications on pain catastrophizing were retrieved from 2010 to December 31, 2020. The number and rate of the annual publications gradually increased totally. Pain (130) was the most productive journal. Meanwhile, Pain ranked first in the frequency (1432) and centrality (0.31) of the cited journals. The most productive country and institution in this frequency field were the USA (642) and the University of Washington (73), respectively. Jensen MP (34) was the most prolific author, and Sullivan MJL (1196) ranked first among the cited authors. In the ranking of frequency in the cited references, the first article was a critical review about pain catastrophizing published by Quartana (100). The keyword ‘Low back pain’ had the highest frequency (556). ‘Total hip’ was identified as a frontier research item for 2016-2020. Conclusion: The findings of this bibliometric study provide the current status and trends in the clinical research of pain catastrophizing and may help researchers to identify hot topics and explore new research directions in this field.